PENGEMBANGAN POJOK LITERASI DALAM MENINGKATKAN KEMAMPUAN LITERASI DASAR SISWA SD NEGERI 1 GULAK GALIK BANDAR LAMPUNG - Elvadola, Connyta; Rahmawati, Endah; Putra, Agung Dian; Asmarani, Yuli (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop a literacy corner to improve students’ basic literacy skills namely reading literacy, science literacy, and mathematics literacy at SD Negeri 1 Gulak Galik in Bandar Lampung. This study employs a research and development (R&D) methodology, comprising the stages of needs analysis, design, development, implementation, and evaluation. Data collection techniques include observation, questionnaires, and documentation. The research instruments consist of observation sheets to assess teachers’ and students’ responses, an expert validation questionnaire, and literacy assessment items covering reading literacy, science literacy, and mathematics literacy, which were analyzed using both qualitative and quantitative descriptive methods. The research results show that the validation by education experts yielded a score of 86% in the “highly acceptable” category, while the validation by literacy experts yielded a score of 90% in the “highly acceptable” category. Teachers’ responses regarding the use of the literacy corner yielded a score of 88% in the “very good” category, and students’ responses yielded a score of 84% in the “very good” category. The results of the effectiveness test showed an average score of 68.5 in the “Moderate” category; observations during implementation indicated an increase in students’ enthusiasm, reading interest, and independent reading habits, which positively impacted their literacy skills. Based on these results, it can be concluded that the developed literacy corner is appropriate and beneficial for supporting the improvement of students’ literacy skills and can be implemented sustainably in elementary schools.